ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK DITINJAU DARI KARAKTERISTIK DOMINANCE, INFLUENCE, STEADINESS, COMPLIENCE (DISC) - Ida Dwi Lestari; Siti Amiroch; Heny Ekawati Haryono (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2021)
Students' mathematical representation skills still need to be improved and developed. Because when faced with questions students experience difficulties and confusion to solve, where to start, which formulas to use and how to solve them. The ability of students in the aspect of mathematical representation is not optimal. Basically, each student also has the characteristics of different ways of thinking that influence the process of representing solving mathematical problems. This study aims to determine the mathematical representation ability of students in terms of Dominance, Influence, Steadiness, Complience (DISC) characteristics. The subjects of this study were students of class X MA Raudlatul Muta'allimin Babat. This research is a qualitative research. Qualitative research concludes the research data in the form of numbers. The data collection method uses a DISC characteristic questionnaire, representation ability test and interviews. The results showed that: (1) Subjects with Dominance characteristics were able to solve all aspects of mathematical representations, namely visual representations in the form of images, equations or mathematical expressions, and written words or texts. (2) Subjects with the characteristics of Influence are able to solve two aspects of mathematical representation, namely visual representations in the form of images and equations or mathematical expressions, whereas in the aspects of words or written texts students have not been able to solve them well. (3) Subjects with Steadiness characteristics are able to solve all aspects of mathematical representations, namely visual representations in the form of images, equations or mathematical expressions, and written words or texts. all questions and able to explain well. (4) Subjects with Compliance Characteristics are able to complete one aspect, namely the visual representation aspect in the form of images, while in the form of mathematical equations or expressions, and written words or texts, students have not been able to complete it properly.